Multi e interdisciplinaridade nos Programas de Pós-Graduação em Ciência da Informação: estudo bibliométrico com dados da Plataforma Lattes - Lança, Tamie Aline (Universidade Federal de São Carlos, 2018)
Information Science arises with the transition between modern science and postmodern science, which originated an integrating knowledge movement called interdisciplinarity. By linking to the fact that it has a complex object of study - information, its interdisciplinary inclination is recognized. With the growth of Postgraduate Programs in Information Science in Brazil and consequent expansion of research in the area, it becomes relevant to identify how the interdisciplinary relationships in the area occur. The potential of the Plataforma Lattes in the development of bibliometric studies is acknowledged for providing a legitimate representation of Brazilian science. The objective of this research was to investigate the multidisciplinary profile and the interdisciplinary relations of Information Science with other areas of knowledge. The research method was of an exploratory nature, with a quantitative approach and involved the use of bliometrics and network analysis techniques. The sample analyzed involed 417 Lattes Curricula of teachers linked to the postgraduate programs, from 2013 to 2017 and of 370 co-authors identified in the scientific production of these teachers, comprising the four-year evaluation period of the Coordenação de Aperfeiçoamento de Pessoal de Nível Superior (CAPES), from 2013 to 2016. As a result, it was characterized the multidisciplinary profile and interdisciplinary relations in Information Science, identifying the areas that provide and those that receive contributions from Information Science. It was concluded that the results contribute to instrumentalize the understanding of interdicisplinarity in the scientific activity of the area, and consequently to its strengthening and visibility as an area of knowledge in the Brazilian National Postgraduate System.
Multi and interdisciplinarity in the Postgraduate Programs in Information Science: bibliometric study with data from the Lattes Platform
Keywords: Ciência da Informação; Interdisciplinaridade; Multidisciplinaridade; Plataforma Lattes; Bibliometria; Information Science; Interdisciplinarity; Multidisciplinarity; Bibliometrics; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO::BIBLIOTECONOMIA::METODOS QUANTITATIVOS. BIBLIOMETRIA; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO::BIBLIOTECONOMIA